Surface modification of oxide capping layers on nickel catalyst for high performance hydrogen applications - Khairul Syafiq Bin Shapuan (Nanyang Technological University, 2024)
This project aims to develop and study the SDC interlayer thickness for the fabrication of Nickel and Yttria-Stabilised Zirconia (Ni-YSZ) anode onto a Lanthanum Strontium Gallium Magnesium (LSGM) electrolyte base. The purpose is to prevent the formation of La2Zr2O7 and LaNiO3 phases due to Ni-YSZ and LSGM reacting during sintering. LSGM pellets were formed using a mechanical press with purchased powder. SDC of varying thickness were deposited onto the LSGM pellets using sputtering method. Ni YSZ was screen-printed onto the SDC coating of the LSGM, thus creating LSGM/SDC/Ni-YSZ half cells. The cells were subjected to EIS readings at 600°C, 700°C and 800°C to simulate intermediate operating temperatures. From EIS readings, it was determined that an SDC thickness of 200nm (SDC 200nm) had the lowest polarisation resistance (Rp). SDC thickness lesser than 200nm had an Rp lower than the reference sample without SDC (Bare LSGM). SDC thickness above 200nm showed to be detrimental to the overall performance of the SOFC. Finally, a 10-hour degradation test was carried out at 800°C between SDC 200nm and Bare LSGM, with SDC 200nm having better results throughout the simulated operation.